Ecommerce Website Development for Melisa Baby and Kids Shop - Elizabeth Kurniawan Ardianto; Ridwan Sanjaya; Bernardinus Harnadi (Soegijapranata Catholic University, 2023)
In the current era of technological development, someone is always demanded to be creative and innovative in their existence in the digital world. The strategies to jump into the digital marketing field are an effective way to market products in an era of an onslaught of technological advances and the addition of the post-COVID-19 pandemic. A part of digital marketing, internet marketing is one form of marketing innovation that utilizes internet technology and creates marketing in the digital world, including among others, social media marketing, content marketing, and online platform marketing [1]. The baby shop business is one of the businesses that can implement digital marketing because the needs of babies are a primary need that must be sufficient. Strategies that can be used to increase sales of baby and children's equipment businesses are developing an ecommerce website that implements plugins, attractive landing page designs, promotion through social media, integration of online transactions, payments, and logistics, and creating a user-friendly website. Implementation of an e-commerce website can increase revenue and facilitate product marketing. This research aims to increase Melisa Baby and Kids Shop sales through ecommerce website creation strategies by utilizing plugins that enhance website functionality. By implementing those strategies, the result to business is gaining more visibility and increased sales by up to 30% based on an interview with owner.